Chemistry students' conceptions of school: A study in the context of social representations theory (Revista Contexto & Educação, 2026)
School is widely understood as a space for learning, social interaction, and identity formation, and has been the focus of studies examining how it is represented by different social groups. This study explores the social representations of “school” among 50 undergraduate chemistry students from the Institute of Chemistry at the University of São Paulo (IQ-USP), enrolled between 2020 and 2021. A multi-method approach was employed, combining prototypical analysis, similarity analysis, and content analysis. Findings indicate that the core of these representations is structured around the notions of “learning” and “teacher,” highlighting the central role of cognitive processes and pedagogical mediation. Peripheral elements, particularly “friendship” and “social interaction,” point to the social dimension of schooling and appear to be shaped by the broader context of the COVID-19 pandemic. Additionally, references to personal development suggest a more comprehensive understanding of school as a space for holistic formation. These results partially diverge from previous literature and reveal a predominantly positive view of school, integrating cognitive, pedagogical, and socio-emotional dimensions. The study contributes to research on teacher education by shedding light on how prospective teachers conceptualize school and how these representations may inform their professional identity development.
Keywords: Social Representations; School; Teacher Education; Chemistry Education; Higher Education